Kedudukan Fatwa Dsn Mui Dalam Penyelesaian Sengketa Ekonomi Syariah Di Peradilan Agama (Studi Putusan Nomor: 386/Pdt.G/2021/Pa.Yk) - Muhammad Khoiru Sa’i; Zaidah Nur Rosidah (TAFAQQUH, 2022)
This study aims to understand the resolution of Islamic economic disputes through litigation in Religious Courts and analyze the position of DSN-MUI Fatwas in court proceedings. The focus is on a case between KJKS BMT Berkah Al-Fath Mulia and Fahmi Akbar Idries Bin Ahmad Mudjib regarding breach of contract (wanprestasi) and surety liability (Borgtocht), adjudicated by the Yogyakarta Religious Court under case number 386/Pdt.G/2021/PA.YK. The research employs a normative method with a library research approach. The collected data is analyzed descriptively to explain the role of DSN-MUI Fatwas in legal considerations for resolving Islamic economic disputes. The findings reveal that the judge utilized DSN-MUI Fatwas in legal considerations as written doctrines reflecting Islamic principles and societal values. In this case, DSN-MUI Fatwa Number 07/DSN/MUI/IV/2000 on mudharabah financing was used to strengthen other legal considerations permissible under legal provisions. This research contributes to clarifying the role of DSN-MUI Fatwas as legal guidelines in resolving Islamic economic disputes in Religious Courts. It enhances understanding of the integration of Islamic law into Indonesia's judicial system.